1999
DOI: 10.1159/000026598
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Protein Kinase C alpha Levels in Drug-Free and Lithium-Treated Subjects with Bipolar Disorder

Abstract: Recent studies suggest that protein kinase C (PKC), particularly the α isoform, plays an important role in the action of lithium. There is, however, little evidence from patients with bipolar disorder (BD) to support this effect. The present investigation carried out comparative studies of PKC levels in platelets obtained from BD subjects including those with and without lithium treatment. All subjects met DSM-IV criteria for BD type I confirmed by structured interview (SCID-IV). Levels of PKC-α isoform in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
0
13
2
Order By: Relevance
“…Soares et al (2000) found a significant decrease in PKC ␣ but not PKC ␤I, ␤II, ␦, and in platelets of lithiumtreated patients compared with control subjects. Whereas the discrepancy between our results and those of Soares et al (2000) could be attributed to previous treatment with lithium, the reasons for discrepancy in our results and those of Friedman et al (1993) and Young et al (1999) are unclear.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Soares et al (2000) found a significant decrease in PKC ␣ but not PKC ␤I, ␤II, ␦, and in platelets of lithiumtreated patients compared with control subjects. Whereas the discrepancy between our results and those of Soares et al (2000) could be attributed to previous treatment with lithium, the reasons for discrepancy in our results and those of Friedman et al (1993) and Young et al (1999) are unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…p values are a, .009; b, .001. Young et al (1999) did not find any differences in PKC ␣ either in membrane or cytosol fractions of platelets between bipolar patients and normal control subjects. Soares et al (2000) found a significant decrease in PKC ␣ but not PKC ␤I, ␤II, ␦, and in platelets of lithiumtreated patients compared with control subjects.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In contrast to putative hyperactive PKC signaling in BD, Young et al [88] did not observe any significant difference in PKCα levels and activity between platelets from control, drug-free BD patients, and lithium-treated BD patients. In another contradictory finding in a recent report, Hayashi et al [61] reported increased PKC activity in response to lithium in cultured adipocytes from patients with BD.…”
Section: Pkc Translocation and Activitymentioning
confidence: 95%
“…It seems also relatively clear that treating mania with a mood stabilizer can reverse the enhancement of platelet PKC activity along with improving the mood in the same patients [90,91]. However, data become more discrepant when different mood states are mixed in the same BPD group (manic, mixed, and depressed states) [92][93][94]. Regarding MDD, two out of three studies reported no change in PKC activity, neither in the membrane nor in the cytosolic fractions [89,94].…”
Section: Abnormalities Of the Pkc System In Patients With Mood Disordersmentioning
confidence: 99%